Management of HIV associated Kaposi's Sarcoma in Malawi - Mlombe, Yohannie (The Medical Association Of Malawi, 2008)
Kaposi's sarcoma is a common malignancy in Malawi and is often managed with single agent vincristine. This article outlines feasible combination chemotherapy for Kaposi's sarcoma in Malawi which should be made more widely available.